DEVELOPMENT OF ACCOUNTING JENGA AS A LEARNING MEDIA TO IMPROVE STUDENTS MOTIVATION - Theresia Lindha Widya Sari; Mimin Nur Aisyah (Jurnal Pendidikan Akuntansi Indonesia, 2017)
This research aimed at: (1) developing Accounting Jenga as a learning media in Accounting Equation material for students in class XI IPS 1 SMA Negeri 1 Prambanan Klaten, (2) measure the feasibility of Accounting Jenga based on the assessment of material expert, media expert, subject practitioner, students’ responses, and (3) measure students’ motivation improvement. This research was Research and Development (RD) adapting the ADDIE model. Data were collected through questionnaires distribution and were analysed using qualitative quantitative method. The results were: (1) average score obtained from Material Expert was 4.83 classified as Strongly Feasible, (2) average score obtained from Media Expert was 4.27 classified as Strongly Feasible, and (3) average score obtained from Subject Practitioner was 4.93 classified as Strongly Feasible. Based on students’ responses, average score obtained in small group tryout was 4.51 classified as Strongly Feasible and average score obtained in field tryout was 4.26 classified as Strongly Feasible. Students’ motivation improved 6.62% from 73.02% to 79.32%. Paired sample t test result showed that the improvement is significant (sig 0.000 and t value 5.287).Keywords: Accounting Jenga, Learning Media, Learning Motivation, Accounting Equation, ADDIE.